2023
DOI: 10.1111/bre.12757
|View full text |Cite
|
Sign up to set email alerts
|

A rift‐scale view at strain partitioning during multiphase rifting: Insights from the Hailar Basin, northeast Asia

Abstract: Many continental rift basins are characterized by multiphase rifting, which is commonly evident in the temporal and spatial variations of strain accumulation (e.g. Bell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 95 publications
(180 reference statements)
0
17
0
Order By: Relevance
“…The second phase rifting during the Berriasian to Barremian (including Tongbomiao Stage and Nantun Stage) became more intense and widespread across the whole rift due to the large-scale rollback of the Paleo-Pacific slab (Figure 2a; Song et al, 2019;Wu et al, 2023). Strain localization took place during the third rift phase (including Damoguaihe Stage and Yimin Stage) and then thermally controlled subsidence dominated, representing the eventual cessation of rifting (Wu et al, 2023). Wu et al (2023) also suggested that a slight change in the predominant fault strike and a series of minor emergent N-S-trending faults suggest that regional/local stress field may have varied during the third rift phase.…”
Section: Highlightsmentioning
confidence: 99%
See 4 more Smart Citations
“…The second phase rifting during the Berriasian to Barremian (including Tongbomiao Stage and Nantun Stage) became more intense and widespread across the whole rift due to the large-scale rollback of the Paleo-Pacific slab (Figure 2a; Song et al, 2019;Wu et al, 2023). Strain localization took place during the third rift phase (including Damoguaihe Stage and Yimin Stage) and then thermally controlled subsidence dominated, representing the eventual cessation of rifting (Wu et al, 2023). Wu et al (2023) also suggested that a slight change in the predominant fault strike and a series of minor emergent N-S-trending faults suggest that regional/local stress field may have varied during the third rift phase.…”
Section: Highlightsmentioning
confidence: 99%
“…Using interval velocities of 5000-6000 m/s for pre-rift basement (including pre-rift strata and crystalline basement), we determine a vertical seismic resolution of ca. 40-50 m. Four key seismic horizons (T5, T4, T22 and T04; Figure 2a; Liu, 2014) and associated controlling faults have been outlined in Wu et al (2023) and are used to generate time-thickness maps to examine the evolution of the syn-depositional fault activity and depocentre during multiphase rifting. The dip angles of major rift-related faults shown on selected seismic profiles were measured on time domain and then calculated through time-depth conversion.…”
Section: Interpretation Of Basement Structuresmentioning
confidence: 99%
See 3 more Smart Citations